Fósforo na água e no sedimento na microbacia hidrográfica do Arroio Lino - Agudo - RS - Pellegrini, João Batista Rossetto (2005)
The natural ecosystems are modificated by human activities, charging the nutrients and sediments transference to aquatic environments. Our objective were to study the phosphorus (P) dynamic in little cracks after rainfall events, its relation with sediments physicalchemicals properties in a catchment with tobacco culture system under different soil management. It was measured sediments concentration, soluble phosphorus (Ps), particulate bioavailable P (Ppd) potentially bioavailable P (Pppb) e total phosphorus (Pt) in water and sediment samples. These samples were collected in several places during tobacco culture cycle (October to February). In sediments it were analysed the maximum capacity of adsorption (Pmax), the constant related to the bound energy (k) and the phosphorus equilibrium concentratrion (CEP), using adsorption and desorption. Using desorption curves, it were calculated the maximum desorption capacity (β) and the rate constant of desorption (λ). In the sediments, it was determined the iron oxides and total organic carbon contents, and granulometric distribution. The water collected from the areas with larger antropic action presented larger sediment and phosphorus concentrations in all forms comparatively that collected from areas with larger forest covering. The sediments collected in the areas less antropic presented smaller contents of Ppb, larger λ and CEP, while the sediments of those areas with more soil use presented larger k, Pt and buffering capacity (Pppb and β). These behavior is related to the tenors of iron oxides in the sediments. The punctual sources pollution modify the phosphorus dynamics significantly, increasing the pollutant potential. For these reasons, the sediments from areas with larger antropic action have high potential of eutrophication of its surface waters, because its support the growth of aquatic microorganisms in the long period.